2023
DOI: 10.18632/aging.205330
|View full text |Cite
|
Sign up to set email alerts
|

Seven oxidative stress-related genes predict the prognosis of hepatocellular carcinoma

Chen Miao,
Xiao He,
Gang Chen
et al.

Abstract: Predicting the prognosis of hepatocellular carcinoma (HCC) is a major medical challenge and of guiding significance for treatment. This study explored the actual relevance of RNA expression in predicting HCC prognosis. Cox's multiple regression was used to establish a risk score staging classification and to predict the HCC patients' prognosis on the basis of data in the Cancer Genome Atlas (TCGA). We screened seven gene biomarkers related to the prognosis of HCC from the perspective of oxidative stress, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that TPP1 is associated with macrophages in HCC [ 34 ], suggesting that there may be a crosstalk of TPP1 between different immune cells. ENO1, which is second only to TPP1 in terms of coefficient in the scoring system, has been shown to promote hepatocarcinogenesis through YAP1-dependent arachidonic acid metabolism and has been implicated in HCC in relation to oxidative stress [ 35 , 36 ]. Additionally, PTTG1 can promote HCC evolution through reprogramming of asparagine metabolism and is a potential therapeutic and diagnostic target for HCC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that TPP1 is associated with macrophages in HCC [ 34 ], suggesting that there may be a crosstalk of TPP1 between different immune cells. ENO1, which is second only to TPP1 in terms of coefficient in the scoring system, has been shown to promote hepatocarcinogenesis through YAP1-dependent arachidonic acid metabolism and has been implicated in HCC in relation to oxidative stress [ 35 , 36 ]. Additionally, PTTG1 can promote HCC evolution through reprogramming of asparagine metabolism and is a potential therapeutic and diagnostic target for HCC [ 37 ].…”
Section: Discussionmentioning
confidence: 99%